EFFECT OF SERVICE QUALITY AND BRAND TRUST ON CUSTOMER SATISFACTION AND CUSTOMER LOYALTY PERTAMINA HOSPITAL BALIKPAPAN - Lenny Meitha Wulur; Theresia Militina; Gusti Norlitaria Achmad (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This research was conducted by Lenny titled "The Effect of Service Quality and Brand Trust on Customer Satisfaction and Customer Loyalty Balikpapan Pertamina Hospital" under the guidance of Prof. Dr. Theresia Militina, M.Siand Dr. Gusti Noorlitaria. A., SE., MM. This study aimed to analyze the influence of service quality and brand trust to customer satisfaction and customer loyalty. The sampling method used in this study is nonprobability Sampling. The sample used in this study were a total of 110 respondents. Analysis of the data used in this study is Partial Least Square with the help of software SmartPLS3.0. result This research shows: (1) Service Quality (X1) positive and significant impact on Customer Satisfaction (Y1), (2) Brand Trust (X2) positive and significant impact on Customer Satisfaction (Y1), (3) Service Quality (X1) positive and significant impact on Customer Loyalty (Y2), (4) Brand Trust (X2) has positive effect but not significant to Customer Loyalty (Y2), (5) Customer Satisfaction (Y1) positive and significant impact on Customer Loyalty (Y2).